Causal Factors Influencing Purchase Intention Body Care Products on Shopee Application of Consumers in Bangkok and Its Vicinity - Ompitakpong, Phornludee; Lekcharoen, Somchai (Journal of Multidisciplinary in Humanities and Social Sciences, 2025)
The article aimed to 1) develop and validate a causal relationship model for purchase intention of body care products on the Shopee application of consumers in Bangkok and its vicinity and 2) study causal factors for purchase intention of body care products on the Shopee application of consumers in Bangkok and its vicinity. This study was quantitative research. The sample was people who had bought body care products on the Shopee application and live in Bangkok and its vicinity—383 people. The tools used in the research were online questionnaires. The statistics used for data analysis included frequency, percentage, confirmatory factor analysis, and structural equation modeling. The results of this research were the development of the causal relationship models, which consisted of 4 components: 1) social media marketing, 2) perceived service quality, 3) trust, and 4) purchase intention. The model was consistent with the empirical data to a significant extent. The statistic showed that CMIN/df = 1.901, GFI = 0.928, AGFI = 0.905, SRMR = 0.028, and RMSEA = 0.049. The final predictive coefficient was 0.82, indicating that the variables in the model can explain the variance of the purchase of body care products on the Shopee application by 82 percent. The Shopee application’s purchase decisions for body care products directly depend on social media marketing and trust. Therefore, entrepreneurs selling body care products should prioritize building consumer trust and leveraging social media marketing to consistently drive purchase intention for body care products on the Shopee application.